2016
DOI: 10.1097/ta.0000000000001163
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of erythropoietin and hepcidin in the regulation of persistent injury-associated anemia

Abstract: Introduction The cause of persistent injury-associated anemia is multifactorial and includes acute blood loss, an altered erythropoietin (EPO) response, dysregulation of iron homeostasis, and impaired erythropoiesis in the setting of chronic inflammation/stress. Hepcidin plays a key role in iron homeostasis and is regulated by anemia as well as inflammation. EPO is a main regulator of erythropoiesis induced by hypoxia. A unique rodent model of combined lung injury (LC)/hemorrhagic shock (HS)/chronic restraint … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…The reduced hemoglobin following LCHS/CS may be the result of a low level of circulating iron. 26 Hepcidin sequesters iron within macrophages preventing the maturation of red blood cells. In addition, while iron deficiency is associated with an increased rate of erythropoiesis, erythroid precursors have been shown to proliferate and then become quiescent without completing the maturation cycle.…”
Section: Discussionmentioning
confidence: 99%
“…The reduced hemoglobin following LCHS/CS may be the result of a low level of circulating iron. 26 Hepcidin sequesters iron within macrophages preventing the maturation of red blood cells. In addition, while iron deficiency is associated with an increased rate of erythropoiesis, erythroid precursors have been shown to proliferate and then become quiescent without completing the maturation cycle.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] In preclinical rodent studies of blunt trauma, hemorrhagic shock and chronic stress, postinjury hypercatecholaminemia is associated with a suppression of bone marrow erythroid progenitor growth, reduced erythroid commitment, an abnormal EPO response, prolonged mobilization of hematopoietic progenitor cells, and dysregulation of iron homeostasis. 11,12 Norepinephrine, a key modulator of hematopoietic progenitor mobilization and an inhibitor of bone marrow erythroid cell growth, also directly stimulates IL-6 release, and several of our prior studies have implicated these cytokines directly in the development of persistent injury-associated anemia. 13,14 Tumor necrosis factor-alpha (TNF-a) and interleukin-6 (IL-6) are both proinflammatory cytokines that influence hematopoiesis and have altered expression following severe trauma.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 Dysfunctional erythropoiesis in a rodent trauma model can be ameliorated with chemical sympathectomy using either propranolol or clonidine, suggesting that a reduction of hypercatecholaminemia improves erythropoiesis. [11][12][13][21][22][23][24][25][26] Prior research has evaluated the postinjury inflammatory state in severely injured trauma patients and demonstrated their erythropoietic dysfunction and iron dysregulation. 27 To validate our preclinical findings and to expand upon our prior study of the postinjury inflammatory state in humans, the purpose of this study was to evaluate additional severely injured trauma patients and determine if there is a relationship between the ISS in trauma patients, and the degree of neuroendocrine activation and systemic inflammation that is related with persistent injury-associated anemia as well as to further characterize the bone marrow response to injury.…”
Section: Introductionmentioning
confidence: 99%
“…25 Previous work in severe trauma and chronic stress has demonstrated that EPO suppresses plasma hepcidin and iron levels remain low and anemia persists. 2627 …”
Section: Introductionmentioning
confidence: 99%